REKALIBRASI LENGKUNG DEBIT (RATING CURVE) DI POS MONJOT UNTUK MASUKAN OPERASI BENDUNG GERAK RENTANG - A. Mucharam, R.
ABSTRACT: Operating gate of Rentang Weirs based upon discharge volume which followed from upstream (Mot fat station) to necessity irrigation water for I hree regency : Majalengka, lndramayu, and Cirebon regency. As for quantity of Motif at discharge calculated based on rating curve equation was publised by BPSSI)A PU since 1982, with looking at water level in Monjot station which continuously monitoring as long as 24 hours. Becoming alteration of Cimanuk river profile in Monjot station where have become degradation at the bottom of river which exactly significance consequency from sand exploitation plant C in upstream, to make last rating curve were not valid anymore for discharge current condition. From last rating curve equation, number of Ho in Monjot station is +24,37 rn where is discharge equal zero, but at present condition for that water level still have discharge . following Monjot station. It is necessary for last rating curve to re-calibrated. Result of re-calibrate i!o give multi rating curves equation where HR is +22,60 in and coefficient correlation is 98,60% within error value is 2,49%. This result of re-calibration rating curve more valid than rating curve ex BPSDA PU (1982).